2021
DOI: 10.2478/raon-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of breast cancer circulating tumor cells in blood after physical and biological type of isolation

Abstract: Background Circulating tumor cells (CTCs) have become an important biomarker in breast cancer. Different isolation tech-niques based on their biological or physical features were established. Currently, the most widely used methods for visualization after their separation are based on immunofluorescent staining, which does not provide the information on the morphology. Materials and methods The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In summary, cytologic evaluation showed that 48.5% (95% CI 41.5–55.4%) of all patients with MBC with evaluable staining results had one or more CTCs identified. Even though cytocentrifugation is a widely used method for depositing cells onto cytology slides and recent studies have shown that Parsortix-harvested cells deposited onto cytology slides via cytocentrifugation have effectively preserved cellular morphology [ 39 ], it is essential to note that this method caused significant loss (~57% on average) of the cells present in the Parsortix ® PC1 System harvests. Given this large observed cell loss, it is possible that a larger proportion of patients with MBC had CTCs present in their harvests, but these cells were simply not retained on the cytology slides.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, cytologic evaluation showed that 48.5% (95% CI 41.5–55.4%) of all patients with MBC with evaluable staining results had one or more CTCs identified. Even though cytocentrifugation is a widely used method for depositing cells onto cytology slides and recent studies have shown that Parsortix-harvested cells deposited onto cytology slides via cytocentrifugation have effectively preserved cellular morphology [ 39 ], it is essential to note that this method caused significant loss (~57% on average) of the cells present in the Parsortix ® PC1 System harvests. Given this large observed cell loss, it is possible that a larger proportion of patients with MBC had CTCs present in their harvests, but these cells were simply not retained on the cytology slides.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, CTCs have been shown to be morphologically heterogeneous and this is presumably caused by the shear stresses in the bloodstream. [ 100,101 ]…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, CTCs have been shown to be morphologically heterogeneous and this is presumably caused by the shear stresses in the bloodstream. [100,101] To gain more insights into the genesis of DU4475 cell protrusions, we characterized the regulation of protrusion formation. These investigations revealed an additional level of phenotypic plasticity, as protrusion growth was dependent on culture time and location within fibrin gel, which also mimics the evolution of cancer cell subpopulations observed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that in the MBC patient cohort, the morphological features of CTCs were dependent on the separation process. CTCs with a preserved cell morphology were detected after physical separation while the identification of the cell morphology was difficult due to the degeneration of CTCs after biological separation [ 111 ]. A comparative study indicated that although the EpCAM-dependent CTC enrichment was superior in terms of specificity compared to label-free CTC enrichment, it is more suitable to choose size-dependent enrichment approaches in consideration of the evaluation of CTC molecular characterization [ 189 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%